Iron Profile and Hematological Parameters in Patients with Advancing Chronic Kidney Disease - Lamichhane, Anit; Bista, Sahara; Rana, Archan Shumsher; Gautam, Dipika; Pokhrel, Sushant; Khanal, Sudip; Gautam, Sujan; Joshi, Govardhan; Shakya, Jyotsna; Thakur, Rajesh Kumar; et al. (Journal of Manmohan Memorial Institute of Health Sciences, 2024)
Background: Iron deficiency anemia is the most common and early complications of chronic kidney disease (CKD) patients. On the other hand, excess iron supplementation induced iron overload, oxidative stress, hypersensitivity reactions and a permissive environment for infectious processes among CKD. Hence this study aims to determine the association of iron profile and hematological parameters with advancing CKD Method: This descriptive cross-sectional study was carried out among 80 CKD patients attending Manmohan Teaching Hospital, Kathmandu. Demographics, anthropometry, blood glucose, RFT, Serum iron profile and complete blood count were measured. Glomerular filtration rate (GFR) was estimated using Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) criteria for staging CKD. Findings: The study included 80 participants out of which 48 (60%) were females and 32 (40%) were males. Overall, 82.5% of CKD patients were presented with anemia. Among the study population, 50% of CKD patients had normal iron status, 41.3% had iron deficiency, and 8.8% had iron overload. Out of total iron deficient individuals, 69.7% was found to have functional iron deficiency and 30.3% was found to have absolute iron deficiency. WBC and platelets were significantly decreased with increased availability of circulating iron and iron stores. Conclusion: The functional iron deficiency worsens the severity of anemia with advancing CKD. However, iron overload in CKD patients is also associated with leucopenia and thrombocytopenia. Thus, regular investigation and monitoring of serum iron profile is required in CKD patients for the prevention from various complications.